2022
DOI: 10.1002/ajmg.a.62647
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic variant in NFIA associated with subdural hematomas mimicking nonaccidental trauma

Abstract: Subdural hematoma (SDH) in infants raises the concern for nonaccidental trauma (NAT), especially when presenting with associated injuries. However, isolated SDH could be caused by multiple etiologies. NFIA (MIM# 600727) encodes nuclear factor I A protein (NFI‐A), a transcription factor which plays important roles in gliogenesis. Loss‐of‐function variants in NFIA are associated with autosomal dominant brain malformations with or without urinary tract defects (MIM# 613735). Intracranial hemorrhage of various typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Another study of injured children found larger subdural depth was associated with rebleeding (Wright et al, 2019). Finally, a previous case report described a child with cerebral atrophy secondary to an NFIA mutation; his SDHs were considered a complication of cerebral atrophy (Wongkittichote et al, 2022). It is plausible that our patient's subdural collections arose from a similar mechanism.…”
Section: Discussionmentioning
confidence: 60%
“…Another study of injured children found larger subdural depth was associated with rebleeding (Wright et al, 2019). Finally, a previous case report described a child with cerebral atrophy secondary to an NFIA mutation; his SDHs were considered a complication of cerebral atrophy (Wongkittichote et al, 2022). It is plausible that our patient's subdural collections arose from a similar mechanism.…”
Section: Discussionmentioning
confidence: 60%
“…Here, we report on two new individuals carrying microdeletions solely affecting NFIA without any other flanking protein-coding sequences. In order to further define the phenotypic effects of NFIA haploinsufficiency, we reviewed the literature and public databases excluding those patients without detailed clinical information or individuals with pathogenic deletions, translocations, inversions, or genetic variants disrupting additional protein-coding sequences [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 23 , 26 , 27 , 28 , 29 ] ( Table S2 ). This careful selection allowed for the identification of a cohort of 24 patients with pathogenic alterations solely involving NFIA .…”
Section: Discussionmentioning
confidence: 99%
“…2 Deletion of NFIA often occurs as part of a multigenic microdeletion, although 20 cases resulting from smaller intragenic deletions or point mutations have been reported. [3][4][5][6][7][8][9][10] Clinical manifestations of NFIA-related disorder are highly variable, but almost always include abnormalities, such as hypoplasia, of the corpus callosum. Macrocephaly and nonspecific but distinct facial features have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Truncation or deletion of NFIA causing haploinsufficiency can result in an NFIA ‐related disorder 2 . Deletion of NFIA often occurs as part of a multigenic microdeletion, although 20 cases resulting from smaller intragenic deletions or point mutations have been reported 3–10 …”
Section: Introductionmentioning
confidence: 99%